Courting can be killer - Flower, Amanda (Flower, Amanda, Amish matchmaker mystery., 2020)
"Some Amish men don't know what's good for them. That's what Millie Fisher told herself when young Ben Baughman set his heart on marrying Tess Lieb. With Tess's father refusing to give his blessing and Tess's ex-boyfriend being a wet blanket, the hapless couple was bound to butt heads more than Millie's Boer goats. But when Ben tragically dies in a mysterious fire, Millie wonders if someone in her hometown of Harvest, Ohio, wanted Ben out of the wedding picture altogether..."--